Internationalisation at home. The experience of doing an internship during the confinement due to COVID-19 in Colombia and Spain (2000-2020) - Cuño Bonito, Justo; Soto Arango, Diana Elvira (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Under the direction of researchers from the Universidad Pedagógica y Tecnológica de Colombia (UPTC) and the Universidad Pablo de Olavide de Sevilla (UPO), this work intends to analyze the experience of the internationalisation of the Doctorate in Education Sciences Rudecolombia, comparing the first in-person internship in the year 2000 with the virtual one that took place in the Covid-19 pandemic period. An analysis of the internationalisation of the at-home curriculum was carried out with the mechanisms that were established in order to reach their members, establishing links that humanize academic relationships with human challenges and virtual realities in the context of cuts to the financing of public universities in Colombia. Using the methods of social history and heuristic analysis of the sources, it is concluded that the doctoral program has from the beginning implemented internationalisation, mobility and research in the curriculum. This virtual internship showed the good practices developedby universities working as a network and the creative capacity of the collective to provide experiences in specific spaces and times, with activities permeated by human affect in distance education, solving problems related to virtual learning as well as human and institutional issues, in addition to those pertaining to the lack of financing for public universities in Colombia.